Uma análise alternativa aos modelos de avaliação tradicionais e aplicações a empresas do varejo cearense - Canamary, Alyne Costa (2016)
The present work intends to confront the traditional theories of valuation with an alternative proposal based on time series techniques to forecast cash flows, relevant to the evaluation process. We conducted case studies of three segments of retail, in order to develop an application of the alternative proposed model. Evaluation results following the two proposals presented differing values, however, greater sensitivity of alternative methodology for the analysis of short-term status as a reference or a base for negotiations in evaluation processes.